A Case Study in PT. XYZ: Aligning Capacity of Information Technology Human Resources in the Headquarter and Subsidiary Office using IT Governance Framework - Asmoro, Andy (Journal of Applied Information, Communication and Technology, 2019)
In this paper will be explained about a Multi Nationed Company which have many branch office around the world and the company has developed and implemented a new approach to strategic planning that better aligns all activities and competency with the corporate bussines goals. Information Technology employee has to improve their knowledge and competency regarding to technology innovation (C. Casado-Lumbreras, 2013). Hopefully this paper could be the initial framework to realize Capacity Building for Information Technology Resources in companies or any other agencies.